Multicultural Design Based on Interpersonal Conflict Resolution Capability - Mangido Nainggolan; Halking Halking; Hidayat Hidayat; Deny Setiawan (Randwick International of Education and Linguistics Science Journal, 2023)
Indonesia is a country that has a society with very diverse cultures and ethnicities and this is often referred to as a homogeneous society. The diversity of ethnicities and cultures creates a diversity of views and treatment in every activity and ritual of life which creates a different color in every cultural celebration. However, recently this ethnic diversity has not had an impact on mutual respect but rather there has been conflict between culture and ethnicity or also known as interpersonal conflict. Where this research will develop and design multicultural learning based on cultural literacy to develop students' abilities in resolving interpersonal conflicts. The specific target to be achieved is the production of a learning design which is realized in the form of a multicultural learning textbook based on cultural literacy which can be used as a common reference for Pancasila and Citizenship Education Departments throughout North Sumatra who are members of the AP3KnI association for the North Sumatra Region. The research method used is the R&D method following the Borg & Gall procedure. The instrument used was an expert validation questionnaire which was analyzed using the Percentage Average Score (PRS), while data analysis related to students' abilities in interpersonal conflict resolution was carried out using qualitative descriptive analysis techniques on the results of observations during observations when the learning process was going well in the classroom. class or outside class. The results of the research show that the textbook design is declared valid and suitable for use as a guide for students in multicultural learning in Citizenship Education courses. The research results also show that the material design in textbooks can develop students' abilities in practicing interpersonal conflict resolution.